Penalaran Matematis Siswa dalam Menyelesaikan Masalah Sistem Persamaan Linear Dua Variabel (SPLDV) berdasarkan Gaya Belajar Kelas VIII A SMP Negeri 5 Tulungagung - Shinta Nur Alviyah; Beni Asyhar (Circle: Jurnal Pendidikan Matematika, 2023)
Research objectives ((1) To describe the mathematical reasoning of students with an auditory learning style in solving the problem of a system of two-variable linear equations (SPLDV) class VIII A of SMP Negeri 5 Tulungagung. (2) To describe the mathematical reasoning of students with a visual learning style in solving problems of a system of two-variable linear equations (SPLDV) class VIII A of SMP Negeri 5 Tulungagung. (3) To describe the mathematical reasoning of students with kinesthetic learning styles in solving problems of a system of two-variable linear equations (SPLDV) class VIII A of SMP Negeri 5 Tulungagung. This study uses a qualitative approach with a case study type of research. Data collection was carried out using observation, questionnaires, tests and interviews. The analysis technique used is data reduction, data presentation and conclusion. The research subjects taken were six students in class VIII A of SMP Negeri 5 Tulungagung, namely two students with an auditory learning style, two students with a visual learning style and two students with a kinesthetic learning style. The results showed (1) Students with an auditory learning style were able to predict what method to use to solve the questions, but were unable to solve the SPLDV questions well. (2) Students with a visual learning style are able to guess what method is used to solve the problem, understand the steps or methods that can be used in solving this problem. Able to solve mathematical problems in a way or method to draw conclusions from the solutions that have been done and be able to check the validity of an argument. (3) Students with a kinesthetic learning style are able to predict what method to use to solve the problem, but do not write it down on the answer sheet. Understand the steps or methods that can be used in solving SPLDV questions. Able to justify the answers obtained by way of substitution.